Break them apart

Algebra Level 2

1 2 × 3 + 1 3 × 4 + 1 4 × 5 + + 1 49 × 50 \large \frac { 1 }{ 2\times 3} +\frac { 1 }{ 3\times 4 } +\frac { 1 }{ 4\times 5 } +\ldots+\frac { 1 }{ 49\times 50 }

If the expression above can be represented in the form of a b \frac { a }{ b } ,where gcd ( a , b ) = 1 \gcd (a,b)=1 , then find ( a + b ) 3 { (a+b) }^{ 3 } .


The answer is 50653.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Noel Lo
May 30, 2015

1/(n*(n+1)) = 1/n - 1/(n+1). So we have 1/2 - 1/3 + 1/3 - 1/4 + 1/4 - 1/5+ ... + 1/49 - 1/50 = 1/2 - 1/50 = 24/50 = 12/25. a=12, b=25. (a+b)^3 = 37^3 = 50653.

Challenge student note: Nice use of telescopic sum.

Bonus question: Can you find the value of summation :

1 1.2.3 + 1 2.3.4 + 1 3.4.5 + 1 48.49.50 = ? \dfrac{1}{1.2.3} + \dfrac{1}{2.3.4} + \dfrac{1}{3.4.5} \dots + \dfrac{1}{48.49.50} = \ ?

Nihar Mahajan - 6 years ago

Log in to reply

t n = 1 n ( n + 1 ) ( n + 2 ) = > 2 t n = ( n + 2 ) n n ( n + 1 ) ( n + 2 ) = > 2 t n = 1 n ( n + 1 ) 1 ( n + 1 ) ( n + 2 ) { t }_{ n }\quad =\quad \frac { 1 }{ n(n+1)(n+2) } \\ =>\quad 2{ t }_{ n }\quad =\quad \frac { (n+2)-n }{ n(n+1)(n+2) } \quad \\ =>\quad 2{ t }_{ n }\quad =\quad \frac { 1 }{ n(n+1) } -\frac { 1 }{ (n+1)(n+2) }

Substituting various values of n: , we get the following equations: 2 t 1 = 1 1.2 1 2.3 2 t 2 = 1 2.3 1 3.4 2{ t }_{ 1 }\quad =\quad \frac { 1 }{ 1.2 } -\frac { 1 }{ 2.3 } \\ 2{ t }_{ 2 }\quad =\quad \frac { 1 }{ 2.3 } -\frac { 1 }{ 3.4 } \quad

.

.

.

.

2 t n = 1 n ( n + 1 ) 1 ( n + 1 ) ( n + 2 ) 2{ t }_{ n }\quad =\quad \frac { 1 }{ n(n+1) } -\frac { 1 }{ (n+1)(n+2) }

Adding all the above equations, we get

2 t n = 1 2 1 ( n + 1 ) ( n + 2 ) = > t n = 1 4 1 2 ( n + 1 ) ( n + 2 ) 2\sum { { t }_{ n } } =\quad \frac { 1 }{ 2 } \quad -\quad \frac { 1 }{ (n+1)(n+2) } \\ =>\sum { { t }_{ n } } \quad =\quad \frac { 1 }{ 4 } \quad -\quad \frac { 1 }{ 2(n+1)(n+2) }

Substituting n = 48, we get

n = 1 48 t n = 1 4 1 2.49.50 = 1 4 1 4900 = 306 1225 \sum _{ n=1 }^{ 48 }{ { t }_{ n } } \quad =\quad \frac { 1 }{ 4 } \quad -\quad \frac { 1 }{ 2.49.50 } \quad =\quad \frac { 1 }{ 4 } -\frac { 1 }{ 4900 } =\frac { 306 }{ 1225 }

This is my reply to the bonus question. I hope my method and answer are correct. @Nihar Mahajan

Manish Dash - 6 years ago

Correct analysis!

Swapnil Das - 6 years ago
Towhidd Towhidd
Jul 26, 2015

1/2x3+1/3x4+1/4x5+1/5x6+1/6x7+1/7x8+.....................+1/49x50 =1/2-1/3+1/3-1/4+1/4-1/5+.........................-1/49+1/49-1/50 =1/2-1/50 =12/25

hence, (a+b)^3=(12+25)^3=37^3=50653

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...